Assessing the Economic Security Implications of Nuclear Power Development in Uzbekistan (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The prospect of developing nuclear power capabilities in Uzbekistan has sparked debates around its potential economic impacts. This study aims to analyze the economic security implications of constructing a nuclear power plant in the country. By employing a mixed-methods approach, incorporating quantitative data analysis and qualitative interviews with subject matter experts, the research investigates the potential benefits, risks, and challenges associated with nuclear power generation in Uzbekistan. The findings suggest that while nuclear power could contribute to energy security and economic growth, significant upfront capital investments, regulatory frameworks, and public acceptance pose challenges. The study underscores the importance of a comprehensive risk-benefit analysis and highlights the need for a robust policy framework to ensure the responsible and sustainable development of nuclear power capabilities in Uzbekistan.